Penerapan Bimbingan Konseling Islam sebagai Upaya Meningkatkan Kesehatan Mental Siswa SMA - haning, Tyashaning; kusuma, mega; Mahasri , Mahasri Shobabiya (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2024)
Guidance Counseling is an activity that originates from human life. Because in life, humans always experience various problems. So you need help from other people to solve the problem. Guidance Counseling is a series of service programs provided to students so that they are able to develop. Students also need good handling. Like deaf children who cannot hear clearly and communicate well. Especially in terms of religious counseling guidance, which aims to provide assistance to individuals in their religious life so that it is in line with the provisions and instructions of Allah SWT so that they obtain happiness in this world and the hereafter. Recently, there has been significant concern regarding the mental health of adolescents due to the increasing prevalence of mental disorders among them, making this group particularly vulnerable. Adolescents' understanding of mental health can be improved through appropriate educational initiatives using appropriate media. Among various media, audiovisual content, especially video, has shown superior effectiveness in increasing teenagers' knowledge. The guidance and counseling teacher's efforts aim to increase teenagers' awareness of mental health by utilizing counseling methods for handling it.